Anti-tyrosinase and antioxidant activity of proanthocyanidins from Cinnamomum camphora. Issue 1 (1st January 2021) - Yang, Haibo; Xu, Pingluo; Song, Wei; Zhai, Xiaoqiao
ABSTRACT: In this study, total phenols (TP) and proanthocyanidins (PAs) in the leaves and branches of Cinnamomum camphora were investigated, and isolated PAs were determined using reversed-phase high performance liquid chromatography electrospray ionization mass spectrometry (HPLC-ESI-MS). The anti-tyrosinase and antioxidant activities were also evaluated. Furthermore, scanning study and dihydroxyphenylalanine (L-DOPA) oxidation were performed to further analyze the inhibition mechanism of PAs on tyrosinase catalytic activity. PAs had strong inhibitory effects on tyrosinase monophenolase activity, with effectively prolonged the delay time and decreased the steady-state of monophenolase activity. For diphenolase activity, PAs both showed reversible and mixed inhibition. Moreover, the PAs showed strong antioxidant activities in scavenging 2, 2-Diphenyl-1-picrylhydrazyl (DPPH), 1, 2ʹ-azino-bis(3-ethylbenzthiazoline-6-sulphonicacid) (ABTS) and the ferric reducing antioxidant power (FRAP) assays. The PAs in leaves showed stronger anti-tyrosinase and antioxidant capacity, suggesting that C. camphora may be a good resource for tyrosinase inhibitors and antioxidants. This study could provide a scientific basis for the resource utilization of C. camphora and the development of new natural tyrosinase inhibitors and antioxidants in medical, cosmetic, food, and agricultural industries.